FOCAL EPITHELIAL HYPERPLASIA: HECK'S DISEASE - Brzeziński Piotr (Our Dermatology Online, 2010)
Heck's disease (focal epithelial hyperplasia) (FEH) is clinically characterized by multiple circumscribed, soft elevated nodules of the oral mucosa. Papules and plaques are usually the color of normal mucosa, but may be pale or, rarely, white. Disease may persist for years, producing a significant reduction in quality of life. Lessions may be located in the area of mucous membranes of the lips, cheeks and tongue. It is believed that the two virus types are responsible for the FEH, are: HPV 13 and HPV 32. Different therapeutic procedures have been reported: surgical excision, laser ablation, cryotherapy, electrocauterization, interferon, retinoic acid, 5% immiquimod.